Differently Collective. Youth Activism in Italian University Associations - Riccardo Guidi (Coordinamento SIBA, 2017)
This paper deals with the “ordinary life” of non-institutional university participation and more specifically addresses Italian university student organizations, a neglected entity in youth participation research. We set this case study in a wider research agenda that critically reviews the use of concepts of “second modernity” to interpret contemporary youth participation and focuses on the situated emerging collective forms of youth participation in times of a complicated transition to adulthood. University stu-dent organizations are empirically studied through a longitudinal panel qualitative analysis (1st round: 2013; 2nd round: 2016) based upon a non-probabilistic sample of organizations and activists in the cities of Pisa and Florence. Both qualitative comparative analysis and qualitative content analysis are conduct-ed. Our situated and exploratory study suggests that the term ‘reflexive’ cannot be opposed to the term ‘collec-tive’ when we focus on (youth) participation. The differently collective participatory style of the in-terviewed youngsters becomes particularly original when the associative strategy includes an emerging economic and professionalizing activity